The Effect of Peplau's Model Application on Sleep Quality of Women Waiting for Breast Biopsy Results - Somayeh Gohari; Zahra Sadat Manzari; HamidReza Behnam Vashani (Mashhad University of Medical Sciences, 2024)
Background & aim: During the waiting period for breast biopsy results, women experience sleep disorders. This study conducted to determine the effect of implementing Peplau's model on sleep quality of women waiting for the results of breast biopsy.Methods: This randomized clinical trial was conducted in 2019 at two educational hospitals in Mashhad, Iran. Women who were eligible to enter the study were randomly assigned to the intervention (n=34) and control groups (n=34) by lottery method. The intervention group received a program based on the Peplau's model, included a face-to-face communication and three telephone follow-ups. The control group received conventional care. Data were collected using Pittsburgh Sleep Quality Index, in three stages of before sampling, before and two weeks after receiving the results. Data were analyzed using Chi-square, t-test and the analysis of variance with repeated measures.Results: The mean score of sleep quality of women was 9.1 ± 3.2 in the intervention and 8.4 ± 2.6 in the control group before sampling. It was 8.2 ± 0.3 in the intervention and 8.3 ± 2.4 in the control group before receiving the result. However, two weeks after receiving result. It was 7.4 ± 2.7 in the intervention and 7.6 ± 2.8 in the control group. The analysis showed statistically significant difference between two groups in terms of sleep quality in different time periods (P=0.01).Conclusion: Considering the positive effect of the Peplau's model application on improving the sleep quality, it is recommended to use this model especially in outpatient care settings.